Respuesta inmune innata y adaptativa frente al SARS-CoV-2. Diagnóstico: PCR y serología - Hunt P, Nicole; Bastías O, Carla (Revista Hospital Clínico Universidad de Chile, 2021)
SARS-CoV-2 infection in the people has been characterized by great variability in the clinical manifestations, ranging from an asymptomatic infection in some individuals to a fatal disease in others. Recently, the importance of human genetics in determining clinical response has been highlighted. Within this context there are patients who don’t become infected despite viral exposure and others who, being young without comorbidities, develop a severe disease. On the other hand, it’s under constant investigation whether the presence of a concomitant primary or secondary immunodeficiency determines a different clinical course.